2022
DOI: 10.32598/bcn.2021.724.8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 12 Hz Extremely Low-frequency Electromagnetic Field on Visual Memory of Male Macaque Monkeys

Abstract: Introduction: Today, humans leave in a world surrounded by electromagnetic fields. Numerous studies have been carried out to discover the biological, physiological, and behavioral effects of electromagnetic fields on humans and animals. Given the biological similarities between monkeys and humans, the goal of the present research was to examine Visual Memory (VM), hormonal, genomic, and anatomic changes, and changes of the amygdala function in the male rhesus macaques who exposed to extremely low-frequency mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Studies on the effect of very low-frequency EMFs (7-75 Hz) on monkeys showed no change in their behavior. Sometimes minor differences in activity and response rates were observed, but no sustained effects were achieved (Kazemi et al, 2022). This experience, therefore, proves that electromagnetic radiation has a negative impact on animals.…”
Section: Discussionmentioning
confidence: 68%
“…Studies on the effect of very low-frequency EMFs (7-75 Hz) on monkeys showed no change in their behavior. Sometimes minor differences in activity and response rates were observed, but no sustained effects were achieved (Kazemi et al, 2022). This experience, therefore, proves that electromagnetic radiation has a negative impact on animals.…”
Section: Discussionmentioning
confidence: 68%
“…It is reported that ELF-MFs can modulate the activity of the human brain cortex [44]. Meta analysis performed by Barth et al [45], which included nine studies, showed a limited significant positive effect of ELF-MFs on the cognitive abilities of exposed subjects; moreover, studies on rats [46] and monkeys [47] also showed that ELF-MFs improved the cognitive abilities of those animals. The observed improvement in cognitive abilities due to ELF-MF stimulation may result from a facilitation of forming new neurons in the hippocampal area, as demonstrated in studies on rats [46].…”
Section: Discussionmentioning
confidence: 99%
“… 140 Kazemi et al have suggested that exposing Wrhesus macaquesistar monkeys to ELF-EMF with 12 Hz frequency and 0.7 μT magnetic intensity for 4 hours/day for 30 days may improve visual memory and, consequently, enhance general memory, which is sought to be caused by a decrease in GR genes expression and plasma cortisol. 141 Also, in a similar study, Kazemi et al exposed Wrhesus macaquesistar monkeys to 12 Hz EL-EMF and magnetic intensity of 0.7 μT for 4 hours/day for 30 days. 142 Based on the findings, 12 Hz ELF-EMF exposure may increase scores of visual working memory (VWM), which translates to improvement in memory.…”
Section: Effect Of Elf-emf Exposure On Nervous System Functionalitymentioning
confidence: 97%